A causal association between amyotrophic lateral sclerosis and atrial fibrillation: a two-sample Mendelian randomization study - Yao, Yiren; Liu, Hongyang; Gu, Yang; Xu, Xiaojin; Zhang, Xiwen (Frontiers in Cardiovascular Medicine, 2024)
Objectives: To look into the connection between amyotrophic lateral sclerosis (ALS) and atrial fibrillation (AF) using Mendelian randomization (MR).Methods: Two-sample MR was performed using genetic information from genome-wide association studies (GWAS). Genetic variants robustly associated with ALS and AF were used as instrumental variables. GWAS genetic data for ALS (n=138086, ncase=27205) and AF (n=1030836, ncase= 60620), publicly available from IEU Open. The specific MR protocols were Inverse variance-weighted (IVW), Simple mode, MR Egger, Weighted mode, and Weight median estimator (WME). Subsequently, the MR-Egger intercept and Cochran Q examine were used to evaluate instrumental variables (IVs)' heterogeneity and multiplicative effects (IVs). In addition, MR-PRESSO analysis was conducted to exclude any potential pleiotropy.The IVW method demonstrated that ALS positively affected AF (OR:1.062, 95% CI (1.004-1.122); P=0.035). Indeed, other MR methods were in accordance with the tendency of the IVW method (all OR＞1), and sensitivity testing verified the reliability of this MR result.Conclusions: This MR study proves a positive causal connection between ALS and atrial fibrillation.Further studies are warranted to elucidate the mechanisms linking ALS and AF.